Type 1 gastric carcinoid tumor: another extrahepatic manifestation of hepatitis C virus infection? - Eser VARDARELİ; Tülay SARIÇAM; Serap IŞIKSOY; Hasan YAVUZ; Ayşegül ÖZAKYOL; Baybora KIRCALI (Turkish Journal of Gastroenterology, 2019)
-